The Business Strategy Analysis of a Forwarding Company in Indonesia - Regina Inderadi; Larasati Adiannisa; Nugroho J. Setiadi (The Winners, 2018)
The aims of this research were to identify key internal and external success factors within the forwarding industry and the organization, and to analyze competitive positioning of a forwarding business in Indonesia in order to obtain its optimal business strategy. Research method applied was qualitative approachusing case study. Respondents consist of 20 managers at Jakarta. Data collection was conducted in October 2017 at Jakarta using questionnaire distribution. The first stage of data analysis mapped company's strengths and weaknesses into Internal Factor Evaluation (IFE) matrix, mapped market opportunities and threats into External Factor Evaluation (EFE) matrix, and mapped competition into Competitive Profile Matrix (CPM) with the application of Expert Choice Software. The results of the external and internal audit were used to generate alternative strategies by applying a Business Competitive Position Matrix, Grand Matrix Strategy, and BCG Matrix. Three alternative strategies were selected from matrices conducted prior to Quantitative Strategic Planning Matrix (QSPM), namely adding the new sub-business unit to serve delivery service for small-sized goods (product development), conduct IT innovation to open opportunities in entering E-Commerce business (market development), and liquidation. The outcome is a product development strategy, which is indicating that the best strategic decision for the future sustainability in the business competition is to add new sub-business unit in small-sized goods delivery.